REAL WORLD DATA; EFFECTIVENESS OF COVID-19 TREATMENT IN SEVERE SYMPTOMS PATIENTS AT RS PKU MUHAMMADIYAH GAMPING IN AUGUST 2022-2023 - Simamora, Patimah; Risdiana, Irma; Khuluq, Muh. Husnul; Perwitasari, Dyah A (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Severe COVID-19 has created significant real-world clinical challenges, particularly in the management of critically ill patients in intensive care units. The disease is often accompanied by serious complications, such as acute respiratory distress syndrome (ARDS), multiple organ damage, and increased risk of mortality, particularly in individuals with risk factors such as advanced age and comorbidities. Real World data provide evidence related to effectiveness as patients are observed from admission to discharge. This study aimed to obtain an overview of the effectiveness of COVID-19 treatment with severe symptoms at RS PKU Muhammadiyah Gamping in August 2022-2023. This observational study used a descriptive research design. Data collection was retrospective and was obtained from medical records. Descriptive analyses were conducted including patient characteristics, drug usage, and therapy effectiveness. This study obtained data from 45 patients who met the inclusion criteria for severe COVID-19 ...